Tariffs, quotas, and trade : the politics of protectionism - Adams, Walter; Institute for Contemporary Studies (San Francisco : Institute for Contemporary Studies, 1979)
This is the first institute book dealing exclusively with international economic problems. Economic problems related to the Third World, and to U.S.- Third World relations, are dealt with in more detail in The Third World: premises of U.S. policy
Includes index.
Includes bibliographical references: p. 307-315.
osc 18/07/2018
Loans
Keywords: Free trade; Protectionism; Tariff; Commercial policy; International economic relations